Choosing the best method for estimating the survival function of inverse Gompertz distribution by using Integral mean squares error (IMSE) - A. Hashim , Mustafa; N. Abood, Suhail (Journal of Economics and Administrative Sciences, 2022)
In this research, we study the inverse Gompertz distribution (IG) and estimate the survival function of the distribution, and the survival function was evaluated using three methods (the Maximum likelihood, least squares, and percentiles estimators) and choosing the best method estimation, as it was found that the best method for estimating the survival function is the squares-least method because it has the lowest IMSE and for all sample sizes.